Antia-Buch versus Franssen-Frechner Technique. Issue 3 (March 2021) - Abdelkader, Rasha; Malahias, Marco; Abdalbary, Sahar Ahmed; Noaman, Ayman
Abstract : Background: We performed a retrospective study comparing 2 patient groups. Each cohort included 22 cases of skin cancer of the external ear. Each patient required resection of the affected part of the external ear, followed by flap reconstruction. Methods: The patients in Cohort A underwent external ear reconstruction with a classic Antia-Buch flap, as described by Antia and Buch in 1967: The defect was closed by mobilizing an advancement flap from the root of the helix (upper ear), which was closed in a V-Y fashion, after a rim of healthy scaphal cartilage was resected to allow approximation of the skin. The patients in Cohort B underwent external ear reconstruction with a modified Antia-Buch flap, as presented by Franssen and Frechner in 2010. Here, a wedge of skin was removed from the ear lobe (lower ear), to allow mobilization of an advancement flap from the caudal end of the ear, to close the defect. Results: Both techniques allowed tension-free closure. Cohort B, however, required less dissection of the ear. The entire cephalic ear remained unaffected and no scaphal cartilage was sacrificed, thus preserving ear width, with scars that were overall less visible. Also, the loss in ear height associated with Cohort B was easily symmetrized by contralateral ear lobe reduction. Conclusions: Cohort B achieved closure with less ear dissection, achieving excellent morphological outcomes. The patients in Cohort B had superior levels of satisfaction with scars and ear symmetry than those in Cohort A.